COVID-19 in Patients With Neuromyelitis Optica Spectrum Disorders and Myelin Oligodendrocyte Glycoprotein Antibody Disease in North America: From the COViMS Registry. Issue 5 (September 2021) - Newsome, Scott D.; Cross, Anne H.; Fox, Robert J.; Halper, June; Kanellis, Pamela; Bebo, Bruce; Li, David; Cutter, Gary R.; Rammohan, Kottil W.; Salter, Amber
Abstract : Background and Objective: To describe the impact of coronavirus disease 2019 (COVID-19) on people with neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody disease (MOGAD). Methods: The COVID-19 Infections in Multiple Sclerosis (MS) and Related Diseases (COViMS) Registry collected data on North American patients with MS and related diseases with laboratory-positive or highly suspected SARS-CoV-2 infection. Deidentified data were entered into a web-based registry by health care providers. Data were analyzed using t -tests, Pearson χ 2 tests, or Fisher exact tests for categorical variables. Univariate logistic regression models examined effects of risk factors and COVID-19 clinical severity. Results: As of June 7, 2021, 77 patients with NMOSD and 20 patients with MOGAD were reported in the COViMS Registry. Most patients with NMOSD were laboratory positive for SARS-CoV-2 and taking rituximab at the time of COVID-19 diagnosis. Most patients with NMOSD were not hospitalized (64.9% [95% CI: 53.2%–75.5%]), whereas 15.6% (95% CI: 8.3%–25.6%) were hospitalized only, 9.1% (95% CI: 3.7%–17.8%) were admitted to the ICU and/or ventilated, and 10.4% (95% CI: 4.6%–19.5%) died. In patients with NMOSD, having a comorbidity was the sole factor identified for poorer COVID-19 outcome (OR = 6.0, 95% CI: 1.79–19.98). Most patients with MOGAD were laboratory positive for SARS-CoV-2, and almost half were taking rituximab. Among patients with MOGAD, 75.0% were not hospitalized, and no deaths were recorded; no factors were different between those not hospitalized and those hospitalized, admitted to the ICU, or ventilated. Discussion: Among the reported patients with NMOSD, a high mortality rate was observed, and the presence of comorbid conditions was associated with worse COVID-19 outcome. There were no deaths reported in the patients with MOGAD, although these observations are limited due to small sample size.